EFEKTIVITAS METODE PEMBELAJARAN PPG TERHADAP PENINGKATAN KOMPETENSI PEDAGOGIK MAHASISWA - Aulia, Hera; Munawwar, Andi Agil; Hakiki, Nurul; Purnama, Sinta; Syamsudduha, St. (Department of Islamic Education Management, 2026)
Teacher Professional Education (PPG) is a strategic government program to improve teacher professionalism, particularly pedagogical competence. Under the Ministry of Religious Affairs' Transformation Plus policy, PPG implementation was accelerated by compressing the duration to 45 days and implementing Learning Management System (LMS)-based learning. This study aims to analyze the effectiveness of LMS-based PPG learning in improving pedagogical competence and the implications of accelerating teacher certification on learning quality. This descriptive qualitative study was conducted at the LPTK UIN Alauddin Makassar through observation, interviews, and documentation studies. The results indicate that LMS-based learning effectively improves PPG students' pedagogical competence, particularly in planning, implementing, and evaluating learning. This effectiveness is supported by structured learning design and academic mentoring, although challenges remain in the form of a high learning load in a short duration. Therefore, strengthening learning design and improving participants' digital literacy are necessary to maintain the quality of LMS-based PPG.